PENGARUH PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DI SMA ANTARTIKA SIIDOARJO - Rosita, Ainur; Ladyawati, Erlin (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
This research supported by time progress more advanced. Where future need people who have high levels of creativity. That is why students for the foreseeable future must be more sharpening the capacity to think creative. But the important role of teacher, no less important that approach learning held at the time. To make students creative thinking, students are faced with the problem open-ended goals not oriented in the final answer but more emphasis on the process of to get answers. The formulation of the research is “can influence open-ended approach of the ability of creative thinking mathematically students?“ the purpose of this research is to know how big the influence of open-ended approach of the ability of creative thinking mathematically students”. In this research to measures the creative thinking mathematically students do with the tests the ability of creative thinking that leads to the creative thinking that: mathematical that: elaboration , flexibility , the problem sensitivity , originality , and fluency. The population in this research is the students of SMA Antartika Sidoarjowith the sample class XI MIPA 3 as a class experiment and XI MIPA 4 as a control class. Research data obtained analyzed using normality test, homogeneity test and t-test. Ho hypothesis research: no influence open-ended approach with conventional lessons in the ability of creative thinking mathematically students in SMA AntartikaSidoarjo academic year 2015-2016, while H1: there is the influence of open-ended approach with conventional lessons in the ability of creative thinking mathematically students in SMA AntartikaSidoarjo academic year 2015-2016. its testing criteria that its tarithmetic<ttable. Of calculation t-test obtained 2,594>1.98932, Ho rejected it means. So that in this study concluded that there is influence open-ended approach towards the ability of creative thinking mathematically students in SMA AntartikaSidoarjo academic year 2015-2016. Keywords: Open-ended approach,creative thinking mathematical.